One Health, One World—The Intersecting Legal Regimes of Trade, Climate Change, Food Security, Humanitarian Crises, and Migration - Kelli K. Garcia; Lawrence O. Gostin (Laws, 2012)
Today’s global health challenges require a multi-sectoral approach in which health is a fundamental value within global governance and international law. “One Health, One World” provides a unified, harmonious vision of global health governance that supports the wellbeing of humans and animals living in a clean and temperate environment. This article focuses on five legal regimes—trade law, food security law, environmental law, humanitarian law, and refugee law—that play a pivotal role in influencing health outcomes and are integral to achieving the One Health, One World vision. International trade, for example, opens markets not only to life-saving products such as vaccines, medicines, and medical equipment, but also to life-threatening products such as tobacco and asbestos. If strengthened and enforced, environmental law can decrease air and water pollution, major causes of death and disability. World hunger has been exacerbated by the global economic crisis and climate change, increasing the urgency for international law to enhance food security. Humanitarian law must similarly be strengthened to protect civilians adequately as the nature of warfare continues to change. Refugee law plays a pivotal role in protecting the health of deeply vulnerable people who lack food, shelter, and social stability. Higher standards and more effective compliance are necessary for international law to realize its full potential to safeguard the world's population.